Fabrication and characterization of the bio-based nanofiber solid facial mask with moisturizing and antioxidant efficacy - Fang Zhang; Haiteng Liu; Xiaoyan Pang; Zhiwen Ding; Weiye Zhang; Guoying Li (Collagen and Leather)
Abstract As consumers prioritize safer and more sustainable skincare ingredients, the traditional facial mask industry faces challenges due to the use of non-biodegradable materials and chemical preservatives that irritate the skin and harm the environment. In the present investigation, an innovative all-biomass solid facial mask was developed using electrospinning technology to incorporate naturally effective ingredients into bio-based fibers made of gelatin and pullulan polysaccharide. This process produced a nanofiber-based, fast-dissolving facial mask with essence uniformly embedded throughout the fibers. Unlike traditional facial masks that rely on preservatives, this solid mask avoids their use while offering excellent water and moisture retention. Owing to its nanostructured architecture and water-soluble fiber materials, it dissolves completely in water within just 7 s. Yak skin collagen peptides incorporated into the nanofiber film demonstrated strong antioxidant activity, scavenging 88.3% of DPPH free radicals. Biocompatibility testing combined with animal skin and eye irritation testing further confirmed the safety of the facial mask. This innovative approach not only supports the sustainable development of environment and resources but also delivers safer, more effective skincare solutions for consumers. Graphical Abstract